Estimation of software projects: a practical case (2009)
This article describes a methodology to estimate and plan software projects and experience in the estimation process, with students of the Software Engineering course of the undergraduate program of the Computer School at the University of Costa Rica. In it students learn methodologies, techniques and software engineering tools and develop a practical project. To estimate the duration of their projects they use the Function Points technique to measure the size of the application and, subsequently, apply different techniques for estimating the duration to plan their projects.